Multi‐Stimuli Nanocomposite Therapeutic: Docetaxel Targeted Delivery and Synergies in Treatment of Human Breast Cancer Tumor. Issue 41 (18th September 2020) - Taheri‐Ledari, Reza; Zhang, Wenjie; Radmanesh, Maral; Mirmohammadi, Seyedeh Shadi; Maleki, Ali; Cathcart, Nicole; Kitaev, Vladimir
Abstract: A versatile breast cancer‐targeting nanocomposite therapeutic combining docetaxel (DXL), polyvinyl alcohol (PVA) network for controlled release, and silica‐protected magnetic iron oxide nanoparticles (Fe3 O4 NPs) for targeted delivery and gold nanoparticles (AuNPs) for plasmonic photothermal therapy (PPTT) is presented in this work. First, the designed nanocomposite is magnetically directed for cancer‐targeted therapy confirmed by computerized tomography (CT) scans. Second, 10% DXL by mass is loaded into PVA, a pH and temperature responsive gel, for controlled release. Third, PPTT is confirmed with Au/Fe3 O4 /PVA‐10%DXL using a prototype circulation system and then for tumor treatment in vivo; Au/Fe3 O4 /PVA‐10%DXL is conveniently directed and the entrapped DXL is selectively released (≈96%) via the interaction of green and near‐infrared (NIR) light with the localized surface plasmon resonance of AuNPs. A 75% cell death is reported from in vitro studies with DXL doses as low as 20 µg mL −1 of Au/Fe3 O4 /PVA‐10%DXL, and a 70% tumor growth inhibition is demonstrated by in vivo experiments with the biosafety studies confirming minimal side effects to other organs. Overall, the developed Au/Fe3 O4 /PVA‐10%DXL has a strong potential to simultaneously enhance CT imaging contrast together with the targeted delivery of DXL. Abstract : A developed therapeutic incorporates docetaxel into a polyvinyl alcohol network for dual‐mode (temperature and pH) controlled release and utilizes silica‐protected iron oxide nanoparticles for magnetically targeted delivery and gold nanoparticles for plasmonic photothermal therapy. The targeted delivery of docetaxel and effective treatment of tumors both in vitro and in vivo confirm a successful design of a promising nanomedicine.